2016
DOI: 10.1002/ecs2.1556
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic in surface waters of urban rivers: concentration, sources, and associated bacterial assemblages

Abstract: Abstract. The ecological dynamics of microplastic (<5 mm) are well documented in marine ecosystems, but the sources, abundance, and ecological role of microplastic in rivers are unknown and likely to be substantial. Microplastic fibers (e.g., synthetic fabrics) and pellets (e.g., abrasives in personal care products) are abundant in wastewater treatment plant (WWTP) effluent, and can serve as a point source of microplastic in rivers. The buoyancy, hydrophobic surface, and long transport distance of microplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
207
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 443 publications
(255 citation statements)
references
References 83 publications
21
207
4
2
Order By: Relevance
“…Betaproteobacteria and against Actinobacteria and Cytophagia on the plastics agrees well with other reports on bacterial communities recovered from microplastics in lotic environments (McCormick et al, 2014(McCormick et al, , 2016. Among the individual substrates, however, no substantial differences were detected, probably because of the low replication and high within-treatment variability, reflecting the influence of stochastic processes and founder effects.…”
Section: Species Sorting In Biofilm Communities On Microplasticssupporting
confidence: 91%
“…Betaproteobacteria and against Actinobacteria and Cytophagia on the plastics agrees well with other reports on bacterial communities recovered from microplastics in lotic environments (McCormick et al, 2014(McCormick et al, , 2016. Among the individual substrates, however, no substantial differences were detected, probably because of the low replication and high within-treatment variability, reflecting the influence of stochastic processes and founder effects.…”
Section: Species Sorting In Biofilm Communities On Microplasticssupporting
confidence: 91%
“…Using the same collection method, McNeish et al () found microplastic concentrations in Lake Michigan tributaries were 2.9 to 89.6 particles/L. Microplastic particles isolated from rivers in the Chicago, Illinois region included common polymer types such as polyethylene, polypropylene, and polystyrene (McCormick et al ). We acknowledge the limited success in identifying the polymer types of particles reported as microplastic.…”
Section: Discussionmentioning
confidence: 99%
“…Discarded plastic debris and microplastic contamination is widespread in surface-water environments and aquatic ecosystems worldwide (Gregory and Ryan 1997;Thompson et al 2004; Barnes et al 2009), including the open ocean, freshwater (streams and lakes), and soils (Law and Thompson 2014;Faure et al 2015;McCormick et al 2016;Rillig and Bonkowski 2018). Microplastics are contaminants of emerging concern and consist of plastic particles smaller than 5 mm (Moore 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Upward of 300 000 microplastics/m 3 have been found in wastewater effluent from urbanized rivers in coastal areas (Dris et al 2015). It is therefore very likely that organisms that either live in, or frequent urbanized coastal areas are at potential risk from microplastic exposures (McCormick et al 2016), with coastal food webs being possibly more susceptible to the trophic transfer of microplastics than those in other habitats (Browne et al 2010).…”
Section: Abundance Of Microplastics In the Environmentmentioning
confidence: 99%